Political theology : a critical introduction - Newman, Saul, 1972- (Cambridge, UK : Polity Press, 2019)
"God is dead, but his presence lives on in politics. In this intellectual tour-de-force, Saul Newman shows how political theology arose alongside secularism, and relates to the problem of legitimising power and authority in modernity. This book will be a crucial text for students, scholars and readers interested political theology"--
The politico-theological problem -- Max Stirner and the ghosts of the secular modern -- God is unconscious : psychoanalysis and political theology -- Auctoritas non veritas : on the sovereign -- Pastoral power and political spirituality : Foucault and political theology -- Economic theology -- Conclusion : the politics of the profane.
Includes bibliographical references and index.
Keywords: Political theology